The Role of Fintech in Improving Service Accessibility at Indonesian Sharia Banks in Pontianak City - Muhammad Faisal; Mansur; Irvan Wobowo W; Febrianawati; Windi Pratiwi (Jurnal Manajemen dan Perbankan (JUMPA), 2026)
This study analyzes the role of fintech in improving the accessibility of financial services at Bank Syariah Indonesia (BSI) in Pontianak City. The background of this study is the gap in access to financial services for small communities that are difficult to reach by conventional banks. This study uses a quantitative approach with a survey method of 150 active BSI customers who use fintech services, selected through purposive sampling. Data were collected using questionnaires and analyzed with multiple linear regression using SPSS to test the effect of the variables of availability, ease of use, and security of fintech services on the variable of financial service accessibility, including ease of access, service coverage, and financial literacy. The results are expected to provide empirical evidence of the effectiveness of fintech in expanding financial access at BSI and measure customer satisfaction with fintech. This study contributes to the literature on sharia fintech with a focus on empirical analysis in the context of BSI customers in Pontianak, while also serving as a reference for stakeholders in developing sharia banking digital strategies to improve services and empower small communities economically. Abstrak - Penelitian ini menganalisis peran fintech dalam meningkatkan aksesibilitas layanan keuangan pada Bank Syariah Indonesia (BSI) di Kota Pontianak. Latar belakang penelitian adalah kesenjangan akses layanan keuangan bagi masyarakat kecil yang sulit dijangkau oleh perbankan konvensional. Penelitian menggunakan pendekatan kuantitatif dengan metode survei terhadap 150 nasabah aktif BSI yang menggunakan layanan fintech, dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan kuesioner dan dianalisis dengan regresi linier berganda menggunakan SPSS untuk menguji pengaruh variabel ketersediaan, kemudahan penggunaan, dan keamanan layanan fintech terhadap variabel aksesibilitas layanan keuangan, termasuk kemudahan akses, jangkauan layanan, serta literasi keuangan. Hasil diharapkan memberikan bukti empiris efektivitas fintech dalam memperluas akses keuangan di BSI dan mengukur tingkat kepuasan nasabah terhadap fintech. Penelitian ini memberikan kontribusi dalam literatur fintech syariah dengan fokus pada analisis empiris di konteks nasabah BSI di Pontianak, sekaligus menjadi acuan bagi pemangku kepentingan dalam pengembangan strategi digital perbankan syariah guna meningkatkan pelayanan dan pemberdayaan ekonomi masyarakat kecil.